Integrated genomic and functional analysis of Streptomyces sp. UP1A-1 for bacterial wilt control and solanaceae yield increase - Kaari, Manigundan; Manikkam, Radhakrishnan; Joseph, Jerrine; Krishnan, Sakthivel; Annamalai, Kishore Kumar; Khan, Abujunaid; Rajput, Vinay; Dastager, Syed Gulam; Dharne, Mahesh S.; Umar, Md; Venugopal, Gopikrishnan; Alexander, Balamurugan (Gene Reports, 2024)
<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Ralstonia solanacearum<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> is one of the most destructive soil-borne pathogen, causing bacterial wilt to the solanaceae vegetables. <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 isolated from healthy solanaceae rhizosphere soil, exhibited the lowest disease incidence and increased fruit yield of solanaceae vegetables. However, the genomic and functional properties of UP1A-1 are unclear. Therefore, we conducted the present study to elucidate the genomic characteristics of UP1A-1 by whole genome sequencing. The results indicate that the genome of <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 consists of 8,252,902 bp and contains 72.42 % G + C. We identified the genes that confer plant growth promoting (PGP) function, which include those involved in siderophore production, indole-3-acetic acid biosynthesis, phosphate solubilization, nitrogen metabolism, and potassium metabolism. We also identified several other genes, such as chitinase, peroxidase, superoxide dismutase, catalase, proline biosynthesis, and glucose dehydrogenase, which are believed to be involved in the control of wilt disease. These genes revealed that the strain UP1A-1 has physiologically adapted to varied environmental conditions and could potentially control both abiotic and biotic stresses.